The Sustainability of Interreligious Dialogue in Indonesia under the Phenomenon of Intolerance by Islamic Populists - Kurniawan Netanyahu; Deri Susanto (Jurnal Dialog, 2022)
From 2016 to 2019, mass protests were organized by the "Islamic Defense Action 212" in Jakarta. Protests carried out by Islamic populists and the widespread use of identity politics have sparked an escalating wave of intolerance that has led to fractures in inter-religious relations in Indonesia. The phenomenon of intolerance described above is one of the main cases that researchers will analyze by tracing its impact on the continuity of inter-religious dialogue in Indonesia. This research was conducted using a descriptive qualitative analysis approach. This research found that there is a threat to inter-religious dialogue, namely the impact of increased intolerance, which has contributed to increasing the attitude of exclusivity from several Muslim groups in Indonesia toward non-Muslim religious communities. If the Islamic populist actions that occurred in 2019 were repeated in the next few years, especially before the political year, it would undermine the order of peace among religious communities in Indonesia, and dialogue between religions would be difficult to implement.  Keywords: Islamic populists, identity politics, religious intolerance, harmony, interreligious dialogue